Populism: noise and wrath - Gutiérrez Vera, Daniel (2014)
Ernesto Laclau, emeritus professor of the  University of Essex, UK, visited Ecuador in March 2012. In his open conference at FLACSO, Quito, Laclau presented his peculiar interpretation of «populism». The present article sketches the main lines of Laclau’s lecture and draws a critique on some of his main theoretical and political tenets.